Dual active protection anticorrosive coating and preparation method thereof
By introducing COF modified polyaniline and disulfide bonded polyurethane into the two-dimensional nanosheet-based anticorrosion coating, the self-healing ability of the coating is achieved, solving the problem of degradation of protective performance of existing coatings after long-term use, significantly extending the service life of the equipment and reducing maintenance costs.
Patent Information
- Application Number
- CN202411857660.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing two-dimensional nanosheet-based anti-corrosion coating is prone to damage and cracking after long-term environmental aging and mechanical damage, resulting in a degradation of protective performance and unable to effectively prevent corrosion of the steel structure.
COF modified polyaniline (C-PANI) is used as the main component of the coating, and the self-healing ability of the coating is achieved by introducing polyurethane with disulfide bonds. The coating can protect itself in a seawater environment, and through the conversion of Fe2+ and the bond exchange of disulfide bonds, it forms a passivation layer and a healing layer to prevent the penetration of corrosive media.
It realizes independent protection and repair of coatings after damage, significantly extends the service life of deep-sea engineering equipment, reduces maintenance frequency and cost, and reduces pollution to the marine environment.
Smart Images

Figure CN119592194A_ABST
Abstract
Description
Technical Field
[0002] The invention belongs to the technical field of marine anticorrosive coatings. Background Art
[0004] With the rapid development of deep-sea engineering, the challenges faced by underwater equipment in extreme marine environments have become increasingly prominent. These equipment are usually exposed to high humidity, high salinity and high temperature environments, and are extremely vulnerable to pitting, crevice corrosion and galvanic corrosion. These corrosion phenomena not only pose a serious threat to the safe operation of equipment, but may also cause environmental pollution and waste of resources. In this context, the corrosion problem of steel structures is particularly prominent, because the main structure of deep-sea engineering equipment requires a large amount of steel to provide support and stability. Therefore, how to effectively solve the corrosion problem of steel structures has become the key to ensuring the long-term safe operation of deep-sea engineering equipment.
[0005] At present, 2D nanosheet-based anticorrosion coatings capable of autonomous protection in seawater (2D-NACS) play an important role in solving the corrosion problem of steel structures due to their excellent performance. 2D nanosheets have a large aspect ratio and excellent physical barrier ability, which enables the coating to effectively resist the penetration and diffusion of corrosive media. However, after long-term environmental aging and external mechanical damage, these coatings will inevitably have defects such as breakage and cracking, which will lead to a decrease in protective performance and make the corrosion problem reappear. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a dual active protection anti-corrosion coating and a preparation method thereof. The coating is a two-dimensional nanosheet-based anti-corrosion coating that can achieve self-protection in a seawater environment. The technical solution adopted by the present invention is as follows: A method for preparing a dual active protection anti-corrosion coating, the specific steps are as follows: Step 1: Preparation of COF-modified polyaniline: 1) Disperse 1.5 g of polyaniline in 750-3000 mL of acetonitrile and ultrasonicate for 1 h to obtain a polyaniline solution; 2) Add 2 mol of 2,6-pyridinedicarboxaldehyde (PDA) and 3 mol of 4,4',4''-(1,3,5-triazine-2,4,6-triyl) triphenylamine (TTA) to the polyaniline solution, and wrap the covalent organic frameworks (COF) obtained by the reaction of PDA and TTA on the surface of PANI through Schiff base reaction under acidic conditions to synthesize COF-modified polyaniline (C-PANI); 3) The synthesized C-PANI is separated by centrifugation, washed with ethanol, and the product is collected and dried to obtain C-PANI.
[0007] Step 2: Preparation of coating: 1) Pour isophorone diisocyanate (IPDI) into a reaction container, heat it to 50°C and pass nitrogen, then drop polytetrahydrofuran (PTMG) into the reaction container, react at 50°C for 30 minutes, then raise the temperature to 80°C and continue the reaction for 3 hours to obtain a prepolymer, bottle the prepolymer and seal it, cool it to room temperature and store it for later use; wherein the molar ratio of IPDI to PTMG is 2:1; 2) Pour the prepolymer and organic solvent into a beaker, add C-PANI, and mix to obtain coating component A; 3) adding 4,4′-dithiodiphenylamine (DTDA) and adipic acid dihydrazide (AD) into an organic solvent and completely dissolving them to obtain coating component B; 4) Adding the coating component B to the coating component A, stirring at 60° C. for 24 hours to obtain a coating having a solid content of 20-50wt%; The molar ratio of IPDI and PTMG in step 1) and DTDA and AD in step 3) is 2:1:0.5:0.5; the amount of C-PANI added is 0.25-1.5wt% of the total mass of IPDI, PTMG2000, DTDA and AD; Step 3: Apply the coating obtained in step 2 on the surface of the substrate and cure it in a vacuum oven at 80° C. for 24 hours to obtain a dual active protective anti-corrosion coating.
[0008] Preferably, the preparation steps of polyaniline (PANI) in step 1 are as follows: 1) Disperse purified aniline and surfactant in dilute hydrochloric acid and form a homogeneous solution A by stirring; the mass ratio of aniline, surfactant and dilute hydrochloric acid is: 1:0.8:(240-300); 2) dilute hydrochloric acid containing 1-3 wt% ammonium sulfate was injected into solution A to initiate polymerization and maintained at room temperature for 10 h; 3) After centrifugal separation, the product was washed with ethanol and deionized water respectively, and then collected and dried to obtain polyaniline (PANI); Among them, it is further preferred that the surfactant in step 1) is cetyltrimethylammonium bromide (CTAB); and the concentration of dilute hydrochloric acid in step 1) and step 2) is 0.01 mol / L.
[0009] Preferably, the PTMG in step 2 is poured into a rotary bottle of a rotary evaporator before use, and then distilled under vacuum at 120° C. for 2 hours. After cooling to 60° C., it is bottled and sealed for storage for later use.
[0010] Preferably, in step 2) and step 3) of step 2, the organic solvent is N,N-dimethylformamide (DMF); The substrate described in step 3 is one of iron, copper, steel, magnesium, titanium, aluminum or their alloys.
[0011] Beneficial effects of the present invention: The present invention uses polyurethane with disulfide bonds as the matrix and introduces modified polyaniline two-dimensional nanosheets to prepare an anti-corrosion coating (C-PANI / PU), that is, a 2D-NACS that achieves self-protection in a seawater environment. When the coating is damaged, seawater touches the substrate, triggering a corrosion reaction to generate Fe 2+ Trigger: ① The first active protection: At the metal / coating corrosion area interface, C-PANI in the coating promotes Fe 2+ Rapidly converted to Fe 3+ , and form a Fe2O3 passivation layer to prevent further intrusion of corrosive media; ② The second level of active protection: The disulfide bonds at the cracks heal through bond exchange, closing the seawater diffusion path and inhibiting the penetration of corrosive media. This process imitates the migration and repair process of skin cells, and eventually the cracks are gradually repaired, restoring the anti-corrosion function of the coating.
[0012] After being damaged, the 2D-NACS coating proposed in the present invention can effectively prevent further corrosion through autonomous protection mechanisms, such as autonomously suppressing local corrosion or repairing cracks, thereby significantly extending the service life of deep-sea engineering equipment. This self-healing ability not only improves the reliability of the equipment, but also reduces sudden failures and safety hazards caused by corrosion. Secondly, the use of 2D-NACS coating can significantly reduce the maintenance frequency and related costs of equipment and improve the overall economic benefits. The reduced frequency of regular maintenance and replacement of damaged parts means savings in operating costs and enhanced sustainability of engineering projects. Finally, 2D-NACS helps protect the marine environment and reduce the negative impact on the marine ecosystem by reducing the release of harmful substances during the corrosion process. This not only conforms to the concept of green development, but also provides strong support for the sustainable use of marine resources.
[0013] The 2D-NACS proposed in the present invention plays an important role and has far-reaching significance in the long-term corrosion protection of deep-sea engineering equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Comparison of low-frequency modulus values after 15 days of electrochemical corrosion test. DETAILED DESCRIPTION
[0015] The technical solution of the present invention is further explained and illustrated in the form of specific embodiments below. Example
[0016] 1. Preparation of COF modified polyaniline: 1) Disperse 1.5 g of purified aniline and 1.2 g of surfactant cetyltrimethylammonium bromide (CTAB) in 450 ml of HCl solution (0.01 mol / l) and form a homogeneous solution by magnetic stirring for 90 minutes.
[0017] 2) Another 60 ml HCl solution (0.01 mol / l) containing 1 g of ammonium sulfate was injected into the above solution to initiate polymerization and kept at room temperature for 10 h.
[0018] 3) After centrifugation (8000 r / min) and washing with ethanol and deionized water three times, the product was collected and further dried at 60 °C to obtain polyaniline.
[0019] 4) Disperse 1.5 g of polyaniline in 1500 ml of acetonitrile and treat with ultrasound for 1 h.
[0020] 5) Then, 2 mol of 2,6-pyridinedicarboxaldehyde (PDA) and 3 mol of 4,4',4''-(1,3,5-triazine-2,4,6-triyl) triphenylamine (TTA) were introduced into the above solution, and the covalent organic frameworks (COF) were wrapped on the PANI surface through Schiff base reaction under acidic conditions to synthesize COF-modified polyaniline (C-PANI).
[0021] 6) After the above solution was centrifuged (8000 r / min) and washed with ethanol three times, the product was collected and further dried at 60 °C to obtain C-PANI.
[0022] 2. Preparation of coating: 1) Pour PTMG2000 into the rotary bottle of the rotary evaporator and then distill it under vacuum at 120℃ for 2 hours. After cooling to 60℃, bottle it and seal it for storage.
[0023] 2) Pour 22g of isophorone diisocyanate (IPDI) into a four-necked flask, heat to 50°C and pass nitrogen, pour 100g of PTMG into a constant pressure dropping funnel and drip into the four-necked flask at a rate of 4 drops per second. The reaction is carried out at 50°C for 30 minutes. Then the temperature is raised to 80°C and the reaction is continued for 3 hours to obtain a prepolymer; the prepolymer is bottled and sealed, cooled to room temperature and stored for later use.
[0024] 3) Pour 122 g of the prepolymer, 1.33 mg of C-PANI and 122 g of solvent N,N-dimethylformamide (DMF) into a beaker and mix to obtain coating component A.
[0025] 4) 6.2 g of 4,4′-dithiodiphenylamine and 4.35 g of adipic acid dihydrazide (AD) were added to 122 g of DMF solvent and completely dissolved to obtain coating component B.
[0026] 5) Add coating component B to coating component A and stir at 60° C. for 24 hours to obtain the coating.
[0027] 3. Curing of coating: The coating was poured into a mold and cured in a vacuum oven at 80°C for 24 hours to obtain a dual active protective anti-corrosion coating.
[0028] Comparative Example 1 1) Before the prepolymer synthesis, PTMG2000 was first poured into the rotary bottle of the rotary evaporator and then distilled under vacuum at 120°C for 2 hours. After cooling to 60°C, it was bottled and sealed for storage.
[0029] 2) Pour 22g IPDI into a four-necked flask, heat to 50°C and pass nitrogen, pour 100g PTMG into a constant pressure dropping funnel and drip into the four-necked flask at a rate of 4 drops per second. The reaction is carried out at 50°C for 30 minutes. Then the temperature is raised to 80°C and the reaction is continued for 3 hours to obtain a prepolymer. The prepolymer is bottled and sealed, cooled to room temperature and stored for later use.
[0030] 3) Pour 122 g of the prepolymer and 122 g of the solvent DMF into a beaker and mix to obtain coating component A.
[0031] 4) 6.2 g of 4,4′-dithiodiphenylamine and 4.35 g of adipic acid dihydrazide (AD) were added to 122 g of DMF solvent and completely dissolved to obtain coating component B.
[0032] 5) Add coating component B to coating component A and stir at 60° C. for 24 hours to obtain the coating.
[0033] 6) Pour the coating into the mold and cure it in a vacuum oven at 80°C for 24 hours.
[0034] Comparative Example 2 1. Preparation of polyaniline: 1) Disperse 1.5 g of purified aniline and 1.2 g of surfactant (hexadecyltrimethylammonium bromide) in 450 ml of HCl solution (0.01 mol / l) and stir magnetically for 90 minutes to form a homogeneous solution.
[0035] 2) Another 60 ml HCl solution containing 1 g ammonium sulfate was injected into the above solution to initiate polymerization and kept at room temperature for 10 h.
[0036] After centrifugation (8000 r / min) and washing with ethanol and deionized water three times, the product was collected and further dried at 60 °C to obtain polyaniline.
[0037] 2. Preparation of coating: 1) Before the prepolymer synthesis, PTMG2000 was first poured into the rotary bottle of the rotary evaporator and then distilled under vacuum at 120°C for 2 hours. After cooling to 60°C, it was bottled and sealed for storage.
[0038] 2) Pour 22g of IPDI solution into a four-necked flask, heat to 50°C and pass nitrogen, pour 100g of PTMG into a constant pressure dropping funnel and drip into the four-necked flask at a rate of 4 drops per second. The reaction is carried out at 50°C for 30 minutes. Then the temperature is raised to 80°C and the reaction is continued for 3 hours to obtain a prepolymer. The prepolymer is bottled and sealed, cooled to room temperature and stored for later use.
[0039] 3) Pour 122 g of the prepolymer solution, 1.33 mg of polyaniline and 122 g of solvent DMF into a beaker and mix to obtain coating component A.
[0040] 4) 6.2 g of 4,4′-dithiodiphenylamine and 4.35 g of adipic acid dihydrazide (AD) were added to 122 g of DMF solvent and completely dissolved to obtain coating component B.
[0041] 5) Add coating component B to coating component A and stir at 60° C. for 24 hours to obtain the coating.
[0042] 6) Pour the coating into the mold and cure it in a vacuum oven at 80°C for 24 hours.
[0043] Effect verification: The electrochemical impedance spectroscopy experiment was performed using a Shanghai Zhenhua electrochemical workstation (CHI760E). The experiment used a standard three-electrode system (the working electrode was the sample, the reference electrode was the Ag / AgCl electrode, and the auxiliary electrode was the platinum electrode). A 3.5wt% NaCl solution was used as the corrosion medium at room temperature. The contact area between the coating to be tested and the corrosion solution was 1.00 cm 2 The amplitude of the applied sinusoidal AC signal is 20 mV and the sweep frequency range is 10 -2 Hz~10 5 Hz. The coating thickness is 80 μm.
[0044] like Figure 1As shown, by comparing the low-frequency modulus values of the electrochemical corrosion test for 15 days, it can be seen that the embodiment with COF-modified polyaniline is better than the comparative example 2 with polyaniline added and the comparative example 1 without adding polyaniline, and its electrochemical corrosion resistance is better. The reason should be that the COF-modified polyaniline has a large number of hydrogen bond receptors on the surface, resulting in better compatibility with the coating matrix, while the unmodified polyaniline has poor dispersibility in the coating, which ultimately leads to reduced anti-corrosion performance.
Claims
1. A method for preparing a dual active protection anti-corrosion coating, characterized in that: The specific steps of this method are as follows: Step 1: Preparation of COF-modified polyaniline: 1) Disperse 1.5 g of polyaniline in 750-3000 mL of acetonitrile and ultrasonicate for 1 h to obtain a polyaniline solution; 2) Add 2 mol of 2,6-pyridinedicarboxaldehyde and 3 mol of 4,4',4''-(1,3,5-triazine-2,4,6-triyl) triphenylamine to the polyaniline solution, and wrap the covalent organic framework obtained by the reaction of 2,6-pyridinedicarboxaldehyde and 4,4',4''-(1,3,5-triazine-2,4,6-triyl) triphenylamine on the surface of polyaniline through Schiff base reaction under acidic conditions to synthesize COF-modified polyaniline; 3) The synthesized COF-modified polyaniline is separated by centrifugation, washed with ethanol, and the product is collected and dried to obtain COF-modified polyaniline; Step 2: Preparation of coating: 1) Pour isophorone diisocyanate into a reaction container, heat it to 50°C and pass nitrogen, then drop polytetrahydrofuran into the reaction container, react at 50°C for 30 minutes, then raise the temperature to 80°C and continue the reaction for 3 hours to obtain a prepolymer, bottle the prepolymer and seal it, cool it to room temperature and store it for standby use; wherein the molar ratio of isophorone diisocyanate to polytetrahydrofuran is 2:1; 2) Pour the prepolymer and the organic solvent into a beaker, add the COF-modified polyaniline, and mix to obtain the coating component A; 3) adding 4,4'-dithiodiphenylamine and adipic acid dihydrazide into an organic solvent and completely dissolving them to obtain coating component B; 4) adding the coating component B to the coating component A, stirring at 60° C. for 24 hours to obtain a coating having a solid content of 20-50wt%; The molar ratio of isophorone diisocyanate and polytetrahydrofuran in step 1) and 4,4'-dithiodiphenylamine and adipic acid dihydrazide in step 3) is 2:1:0.5:0.5; the amount of COF modified polyaniline added is 0.25-1.5wt% of the total mass of isophorone diisocyanate, polytetrahydrofuran, 4,4'-dithiodiphenylamine and adipic acid dihydrazide; Step 3: Apply the coating obtained in step 2 on the surface of the substrate and cure it in a vacuum oven at 80° C. for 24 hours to obtain a dual active protective anti-corrosion coating.
2. The method for preparing a dual active protection anti-corrosion coating according to claim 1, characterized in that: The preparation steps of polyaniline in step 1 are as follows: 1) Disperse purified aniline and surfactant in dilute hydrochloric acid and form a homogeneous solution A by stirring; the mass ratio of aniline, surfactant and dilute hydrochloric acid is: 1:0.8:(240-300); 2) dilute hydrochloric acid containing 1-3 wt% ammonium sulfate was injected into solution A to initiate polymerization and maintained at room temperature for 10 h; 3) After centrifugal separation, the product was washed with ethanol and deionized water respectively, and then collected and dried to obtain polyaniline.
3. The method for preparing a dual active protection anti-corrosion coating according to claim 2, characterized in that: The surfactant in step 1) of step 1 is hexadecyltrimethylammonium bromide.
4. The method for preparing a dual active protection anti-corrosion coating according to claim 2, characterized in that: The concentration of dilute hydrochloric acid in step 1) and step 2) of step 1 is 0.01 mol / L.
5. The method for preparing a dual active protection anti-corrosion coating according to claim 1, characterized in that: The polytetrahydrofuran in step 2 is poured into a rotary bottle of a rotary evaporator before use, and then distilled under vacuum at 120° C. for 2 hours. After cooling to 60° C., it is bottled and sealed for storage for later use.
6. The method for preparing a dual active protection anti-corrosion coating according to claim 1, characterized in that: The molecular weight of polytetrahydrofuran is 2000.
7. The method for preparing a dual active protection anti-corrosion coating according to claim 1, characterized in that: In step 2) and step 3) of step 2, the organic solvent is N,N-dimethylformamide.
8. The method for preparing a dual active protection anti-corrosion coating according to claim 1, characterized in that: The substrate described in step 3 is one of iron, copper, steel, magnesium, titanium, aluminum or their alloys.
9. A dual active protection anti-corrosion coating prepared according to the method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing high-performance fluoro-carbon anticorrosive coating through grafting of conducting polymer onto carbon nanotube
CN104098944A
Method for synthesizing chiral polymer through chiral nanochannel induction based on MOF (Metal Organic Framework) and application
CN115248244A
Bionic self-repairing, antifouling and anticorrosive multifunctional coating and preparation method thereof
CN115746689A
Intelligent metal frame-conductive polymer anticorrosive coating and preparation method and application thereof
CN116145206A
New composites for extraction of metal or contaminating chemical species
US20200261885A1